Digital Marketing and Marketing Communication Strategy at Ciwaringin Cirebon Batik Umkm as a Challenge in Technological Development - Desrizal; Iva Mas Uva; Eva Ariati; Endah Fantini (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
Micro, Small and Medium Enterprises are businesses that play an important role in the national economy. Currently, MSMEs are intensively implemented in various regions in Indonesia. One area that runs this business is Batik Ciwaringin Cirebon, where many MSMEs have been established. The rapid development of information technology has an impact on society in supporting various business activities, both large and small, so that they can be recognized globally. The most obvious impact is that apart from being known, it can also increase sales volume and profits. Digital Marketing is a marketing medium that has a huge influence. By using digital marketing, in this case social media. The method used in this research is normative legal research. Normative legal research, namely a search based on literature or extracting documents and library materials or document studies, which is carried out in an effort to obtain the necessary data relating to the problem